PENGARUH PELATIHAN KERJA, PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS CIPTA KARYA KABUPATEN BANYUMAS - Laila Nur Ajizah; Suyoto Suyoto; Hengky Widhiandono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This study aimed to determine the effect of job training, career development and work environment on the performance of employees in Department of Human Settlements Banyumas regency, either partially or simultaneously. The method used in the sampling is purposive sampling, the sampling was based on the consideration to fit the study criteria in order to increase the accuracy of the sample. The analysis method used is multiple linear regression with the significant level (α) 0.05. The results of this study concluded that the positive effect of job training on the performance of employees in the Department of Human Settlements Banyumas regency, with a significant value of 0.031 is less than 0.05. Career development positive influence on the performance of employees in the Department of Human Settlements Banyumas regency, with a significant value of 0.000 is less than 0.05. The work environment positive influence on the performance of employees in the Department of Human Settlements Banyumas regency, with significant value of 0.000 is less than 0.05. Job training, career development and work environment simultaneously affects the performance of employees in the Department of Human Settlements Banyumas regency, with a significant value of 0.000 is less than 0.05. Advice for leaders should work to improve the training of civil servants stationed appropriate initial education field and conducted the training as well as suggestions for training held in accordance with the needs of employees so that employees fully understand their duties and functions. To enhance the career development of employees should know the position / employee positions will get next. To improve the work environment should provide a place of their own to save the document to make it look more presentable. To improve the performance of the three points above should be met then the performance of employees will increase. Keywords: Job Training, Career Development, Work Environment and Employee Performance